ANALYSIS OF PROTECTION SYSTEM ON MOTOR 6 KV CIRCULATING WATER PUMP PLTU PANGKALAN SUSU OMU - Oktarino Simbolon; Hamdani; Siti Anisah (Sean Institute, 2022)
PLTU Pangkalan Susu uses seawater as the main coolant to condense the turbine output steam into water in the condenser. This seawater is pumped into the condenser by using a Circulating Water Pump (CWP) which is located at the CWP house. CWP is an equipment to supply water to the power plant system, either as cooling water or as water is processed into demin water in a water treatment plant. In operation, this CWP motor is equipped with safety equipment that functions to protect the motor from any disturbances that will occur while the disturbance can occur in any time and it is destructive so that the motor can be secured as early as possible